2018
DOI: 10.1177/1687814018779728
|View full text |Cite
|
Sign up to set email alerts
|

Udwadia–Kalaba theory for the control of bulldozer link lever

Abstract: We propose to apply Udwadia-Kalaba theory to the bulldozer dynamics analysis. The bulldozer system is divided into several subsystems by this approach, which simplifies the modeling process for multi-link mechanism. Based on this approach, the constraints are classified into structure constraints and performance constraints. Structure constraints are used to set up dynamic model without regard for trajectory. Performance constraints are the desired trajectory. Then, according to the equation of motion of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The formulation can be used to model a mechanical system as a system of rigid bodies, with geometrical constraint equations governing their physical kinematical motions. Previous investigations of this dynamic modelling approach [6,7,8] showed convincing agreement of simulated system dynamic results with reference data. Udwadia and Phohomsiri in [9] note that alternative analytical formulations of constrained system motion were offered by Gibbs and Appell, Gauss and Dirac, however emphasise that a key feature of the U-K formulation is that it may provide an explicit set of equations for generic constrained systems.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The formulation can be used to model a mechanical system as a system of rigid bodies, with geometrical constraint equations governing their physical kinematical motions. Previous investigations of this dynamic modelling approach [6,7,8] showed convincing agreement of simulated system dynamic results with reference data. Udwadia and Phohomsiri in [9] note that alternative analytical formulations of constrained system motion were offered by Gibbs and Appell, Gauss and Dirac, however emphasise that a key feature of the U-K formulation is that it may provide an explicit set of equations for generic constrained systems.…”
Section: Introductionsupporting
confidence: 55%
“…In the aforementioned studies [6,7,8,14], the U-K formulation was applied to model rigid-body systems. Various studies have discussed and explored methodologies of applying the U-K formulation to deal with flexible systems.…”
Section: Introductionmentioning
confidence: 99%
“…acceleration constraints brought into play to ensure that the system satisfies the geometric constraints it is subjected to. This dynamic modelling approach has also previously been investigated by Nielsen et al [14], Li et al [15] and Xu et al [16] who all found convincing agreement of simulated system dynamic results with reference data. In 2019, previous work of the authors [7] provided an application study of the Udwadia-Kalaba modelling approach to a rigid nonlinear planar crank-slider linkage mechanism.…”
Section: The Udwadia-kalaba Mbd Modelling Approachmentioning
confidence: 68%
“…The applications of the Udwadia control was extensively reported in recent years. [31][32][33][34][35][36] However, Udwadia control does not consider any uncertainty that is inevitable in the actual mechanical systems. Motivated by these reasons, a robust control is designed based on the frame of the Udwadia control in this paper.…”
Section: Introductionmentioning
confidence: 99%